Entrepreneurial Competencies, Business Coaching and Business Success among Women Micro-entrepreneurs - Moin, Shahrunnizan; Idris, Mohd Mahfudz; Bakar, Saridan Abu (Advances in Social Sciences Research Journal, 2024)
The critical contribution of women micro-entrepreneurs to the growth and development of micro-businesses worldwide, particularly in Malaysia, cannot be overstated. These women generate income and employment opportunities, critical to economic progress. However, to ensure their continued success, it is essential to identify the key factors that contribute to this achievement. Additionally, the role of women micro-entrepreneurs has evolved, and they now require additional competencies beyond their traditional skill set to meet the challenges of the business world. Therefore, business coaching is an indispensable tool for enhancing these competencies, directly influencing their business success. For this study, we employed quantitative research methods to test sixteen hypotheses related to entrepreneurial competencies and the perceived usefulness of business coaching in influencing the business success of women micro-entrepreneurs. The data was collected through a selfadministered questionnaire completed by 261 women micro-entrepreneurs who participated in business coaching sessions. We used a cluster sampling technique to select the samples. Our findings showed that women microentrepreneurs typically start businesses between the ages of thirty-one and forty to achieve work-life balance and support their families. Many have children aged five to twelve and limited education, making entrepreneurship more appealing than traditional employment. Over half of the women micro-entrepreneurs had launched a business before and faced challenges sustaining their ventures. Moreover, our study demonstrated that commitment, conceptual, opportunity, and relationship competencies significantly influenced the business success of women micro-entrepreneurs, making them critical predictors of their success. This study also found that the perceived usefulness of business coaching plays a moderating role in the relationships of strategic, commitment, conceptual, and relationship competencies toward the business success of women micro-entrepreneurs. Therefore, strategic, commitment, conceptual, opportunity, and relationship competencies, along with the perceived usefulness of business coaching, are critical to the business success of women micro-entrepreneurs in Malaysia.